BENTURAN BUDAYA TRADISI MODERNITAS DALAM CERPEN-CERPEN KALIMANTAN TIMUR - Diyan Kurniawati (LOA: Jurnal Ketatabahasaan dan Kesusastraan, 2018)
It discusses about the process of tradition clash presented in East Kalimantan short stories. It analyzes the cause and effect of the clash using the theory of the sociology of literature. It studies about how the icons of tradition and modernity defend their own culture. The one who represents those icons will be studied further as well. The result shows that people who represent those two icons involve in a contest because of different cultures brought by each of them. It also reveals that the cultural clash can be frontal or not. That different situation depends on each icon’s struggle defending their cultural values.